Natural regeneration potential of Madhupur National Park, Bangladesh - Rahman, Md Rayhanur; Hossain, MK; Hossain, Md Akhter; Hasan, Mohammad Emran (Bangladesh Journal of Botany, 2020)
Natural regeneration is an essential tool to evaluate the overall health of a forest ecosystem. Natural regeneration of the tree species in Madhupur National Park showed 47 regenerating tree species among which Shorea robusta has maximum density (18,046 seedlings per ha) followed by Aporosa sp., whereas minimum density (19 seedling per ha) was recorded for Cassia nodosa, Litsea glutinosa, Grewia asiatica and Syzygium cumini, respectively. Relative density, relative frequency and relative abundance were estimated to assess the Importance Value Index (IVI) of the seedlings of different tree species. IVI of S. robusta was highest (66.25 out of 300) followed by Mallotus philippensis (27.33). G. asiatica, Derris robusta, and L. glutinosa showed the lowest IVI (0.93) among the regenerating tree species. Distribution of seedlings into different height classes showed that maximum number (31.4%) of seedlings in the height range of 50 - <100 cm. Among the recorded seedlings, Protium serratum showed maximum (11%) recruitment success. Alien invasive species, pineapple and banana based participatory agroforestry, frequent occurrence of fire, extensive collection of fuelwood and litter are the potential threats to the natural regeneration of Madhupur National Park.